Respuesta :
Answer:
A. the graph of a quadratic function y = (1/4)(x+3)(x-4)
Step-by-step explanation:
(1/4)(x+3)(x-4) = 0
x+3 = 0 or x-4 = 0
x = -3 or x = 4
For the others:
B. -(1/4)(x-3)(x+4) = 0
x-3 = 0 or x+4 = 0
x = 3 or x = -4
C. -(x+3)(x+4) = 0
x+3 = 0 or x+4 = 0
x = -3 or x = -4
D. (x-3)(x-4) = 0
x-3 = 0 or x-4 = 0
x = 3 or x = 4
Answer:
A. the graph of a quadratic function y = (1/4)(x+3)(x-4)
Step-by-step explanation:
(1/4)(x+3)(x-4) = 0
x+3 = 0 or x-4 = 0
x = -3 or x = 4
For the others:
B. -(1/4)(x-3)(x+4) = 0
x-3 = 0 or x+4 = 0
x = 3 or x = -4
C. -(x+3)(x+4) = 0
x+3 = 0 or x+4 = 0
Step-by-step explanation: